2013
DOI: 10.1186/1477-5956-11-19
|View full text |Cite
|
Sign up to set email alerts
|

A SELDI mass spectrometry study of experimental autoimmune encephalomyelitis: sample preparation, reproducibility, and differential protein expression patterns

Abstract: BackgroundExperimental autoimmune encephalomyelitis (EAE) is an autoimmune, inflammatory disease of the central nervous system that is widely used as a model of multiple sclerosis (MS). Mitochondrial dysfunction appears to play a role in the development of neuropathology in MS and may also play a role in disease pathology in EAE. Here, surface enhanced laser desorption ionization mass spectrometry (SELDI-MS) has been employed to obtain protein expression profiles from mitochondrially enriched fractions derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…So far, there are several proteomic and biochemical multi-step technologies used for discovery and validation of biomarkers, such as SELDI-ToF MS, LC-MS/MS, 1D PAGE, and Western blot. For the current research, SELDI-ToF MS was preferred because it is an effective array technology, allowing complex analysis of biological materials and providing a rapid protein expression profile useful for biomarker identification [ 21 , 22 ]. Furthermore, SELDI-ToF MS technology has been successfully applied in biomarker discovery for a number of cancer types, such as acute myeloid leukemia [ 23 , 24 ], pancreatic cancer [ 25 ], lung cancer [ 26 , 27 ], ovarian cancer [ 28 ] and gastric adenocarcinoma [ 29 ], but insufficiently reported in glioblastoma [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, there are several proteomic and biochemical multi-step technologies used for discovery and validation of biomarkers, such as SELDI-ToF MS, LC-MS/MS, 1D PAGE, and Western blot. For the current research, SELDI-ToF MS was preferred because it is an effective array technology, allowing complex analysis of biological materials and providing a rapid protein expression profile useful for biomarker identification [ 21 , 22 ]. Furthermore, SELDI-ToF MS technology has been successfully applied in biomarker discovery for a number of cancer types, such as acute myeloid leukemia [ 23 , 24 ], pancreatic cancer [ 25 ], lung cancer [ 26 , 27 ], ovarian cancer [ 28 ] and gastric adenocarcinoma [ 29 ], but insufficiently reported in glioblastoma [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A further indication of the important role played by the PTP in MS and its activation by ROS is provided by the observation that axonal damage of mice undergoing experimental autoimmune encephalomyelitis is reduced by genetic ablation of p66 Shc [ 194 ]. Importantly, a proteomic study of experimental autoimmune encephalomyelitis identified the ATP synthase dimer-forming subunit e differentially expressed [ 195 ]. Moreover, mutations at the level of the genes encoding subunits a and A6L were observed in MS patients [ 196 ].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…The potential for utilization of protein microarrays in analysis of renal mitochondria could be in high throughput monitoring of selected pathways by analysis of multiple, predefined set of proteins. Arrays based on mass spectrometric detection of proteins bound to affinity surfaces (surface-enhanced laser desorption and ionization, SELDI) have been used for analysis of brain mitochondria 66,67 . Chips with wide range of surfaces are available for SELDI.…”
Section: Methods For Analysis Of Mitochondrial Proteomementioning
confidence: 99%